Perilaku Efektif Guru dalam Melaksanakan Kegiatan Pembelajaran Individu secara Klasikal - M Mustain (PROGRESSA: Journal of Islamic Religious Instruction, 2018)
Effective classroom teachers don't have many problems, while ineffective classroom teachers are characterized by continuous disruption and chaos. By observing classroom teachers who are effective and ineffective. A good teacher is a teacher who in his PBM is able to inspiring teaching students, he is able to turn on great ideas, great desires for his students, able to develop creative and innovative traits. Based on the focus of the study, this study aims to describe the Effective Behavior of Teachers in Implementing Individual Learning Activities in a classical manner. The teacher's approach is the process, method or action that is approached by a teacher to students to create an effective and efficient learning process, in teaching, the teacher must be clever in using a wise and wise approach, the teacher's view of students will determine attitudes and actions. For teachers, the ability to apply the principles of learning in the learning process will help improve the effectiveness of learning management which in the end can be achieved with the learning objectives formulated.